2003
DOI: 10.1103/physreve.68.031706
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution x-ray study of the nematic–smectic-Aand smectic-A–smectic-Ctransitions in liquid-crystal–aerosil gels

Abstract: The effects of dispersed aerosil nanoparticles on two of the phase transitions of the thermotropic liquid crystal material 4-n-pentylphenylthiol-4'-n-octyloxybenzoate (8S5) have been studied using high-resolution x-ray diffraction techniques. The aerosils hydrogen bond together to form a gel which imposes a weak quenched disorder on the liquid crystal. The smectic-A fluctuations are well characterized by a two-component line shape representing thermal and random-field contributions. An elaboration on this line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 19 publications
1
32
2
2
Order By: Relevance
“…The instrumental resolution does not allow for the detailed line shape analysis carried out by Clegg et al for the SmA-SmC transition of 8S5 [9]. Figure 1 illustrates the line shapes in the SmA [1:5 K above T C , Fig.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The instrumental resolution does not allow for the detailed line shape analysis carried out by Clegg et al for the SmA-SmC transition of 8S5 [9]. Figure 1 illustrates the line shapes in the SmA [1:5 K above T C , Fig.…”
mentioning
confidence: 95%
“…While theoretical predictions have not yet been formulated, the experimental evidence points towards a minimization of the random disorder effects, possibly due to the long-range interactions driving the transition. The recently published x-ray diffraction experiments [9] on mixtures of 8S5 with silica nanoparticles revealed that the weak coupling of the liquid crystal with the hydrophilic aerosil surface does not influence the overall molecular orientation and the character of the transition [9]. Contrary to these results, dielectric spectroscopy measurements on the SmA-SmC phase transition of the liquid crystal S--[4-(2 0 -methyl butyl) phenyl 4 0 -n-octylbiphenyl-4-carboxylate] (CE8) containing dispersed silica aerosils demonstrated that aerosils strongly affect the transitional behavior [10].…”
mentioning
confidence: 99%
“…[7] In certain liquid crystal systems, as the temperature is lowered below the SmA phase a transition to a tilted or smectic-C (SmC) molecular phases occurs; in a previous study, the smectic correlation lengths have been found to either saturate or diminish on cooling into the SmC phase. [8] Recently, the role of QRD on tilted smectics (SmC) has been further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…al. [8] presented high-resolution X-ray diffraction data that suggested that both the SmA and SmC phases and phase transitions were largely unaffected by the random fields originating from the aerosil gel network. This finding is also in disagreement with the results of subsequent lower resolution X-ray diffraction studies of doping-induced trends observed for 8 5 S [10] and with the phenomenology deduced from studies of a number of other LC-aerosil gel systems.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the phase transitions and the dynamics and structure of these dispersions have been studied by e.g. theoreticians [4][5][6], calorimetry [7,8], NMR [9], X-ray scattering [10][11][12], light scattering [13,14], computer simulations [15], and ESR [16]. Given the large number of papers in this field, the selection in this introduction should be considered indicative.…”
Section: Introductionmentioning
confidence: 99%